2020
DOI: 10.1016/j.ensci.2020.100262
|View full text |Cite
|
Sign up to set email alerts
|

Out-patient neurological disorders in Tanzania: Experience from a private institution in Dar es Salaam

Abstract: Background and introduction Low and middle-income countries (LMIC) have a considerable burden of neurological disorders. Available profile of neurological disorders in our environment is biased towards neurological admissions. There is a paucity of data on out-patient neurological conditions in sub-Saharan Africa. Objective To determine the frequency and demographic data of neurological illnesses being managed at the adult out-patient neurology clinic of the Aga Khan Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
(68 reference statements)
3
9
0
Order By: Relevance
“…The top 5 neurological disorders were epilepsy (23.0%), peripheral neuropathies (19.6%), movement disorders (14.7%), cerebrovascular diseases (11.1%) and headache disorders (7.7%), these contributed to 76.1% of the entire cohort. Broadly, the spectrum of cases in our cohort is comparable to other studies done in Africa and high -income countries [ [6] , [7] , [8] , [9] , [10] ]. There are however differences in frequency ranking of specific neurological disorders in these studies compared with ours.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The top 5 neurological disorders were epilepsy (23.0%), peripheral neuropathies (19.6%), movement disorders (14.7%), cerebrovascular diseases (11.1%) and headache disorders (7.7%), these contributed to 76.1% of the entire cohort. Broadly, the spectrum of cases in our cohort is comparable to other studies done in Africa and high -income countries [ [6] , [7] , [8] , [9] , [10] ]. There are however differences in frequency ranking of specific neurological disorders in these studies compared with ours.…”
Section: Discussionsupporting
confidence: 88%
“…There are however differences in frequency ranking of specific neurological disorders in these studies compared with ours. For instance, while epilepsy was the leading disorder in our series, Sarfo et al [ 10 ] found cerebrovascular diseases as the topmost neurological disorder in Kumasi, Ghana while Adebayo et al [ 6 ] found headache disorders in Tanzania. This trend may reflect differences in referral patterns across countries and in-hospital referral policies for neurological case management.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While there are no recent research studies conducted to determine the changes in prevalence, the most recent survey in Tanzania looked at the out-patients neurological conditions in a private institution and found that 3.5% of the observed cases (41/1186) had Alzheimer's disease (31.7%) and vascular dementia (43.9%) (Adebayo et al, 2020). Also, in another study to diagnose the presence of delirium in 506 patients admitted in a hospital in Tanzania, 18.7% (95/506) had dementia (Paddick et al, 2018).…”
Section: The Epidemiology and Dementia Burden In Tanzaniamentioning
confidence: 99%
“…The first risk factor observed in the Tanzanian context is age. As age progresses, the risk of Alzheimer's disease, vascular dementia and many other dementias rises drastically (Adebayo et al, 2020;Paddick et al, 2018;Paddick, Mkenda, et al, 2015).…”
Section: Possible Risks Factors and Challengesmentioning
confidence: 99%